Anticorrosive composition, anticorrosive sheet and anticorrosion method for structural steelwork
Patent Information
- Application Number
- JP2023129460
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-08
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-08-08
AI Technical Summary
【0010】 本発明によれば、防食効果に優れる防食組成物、防食用シート及び鋼構造物の防食方法が提供される。
Smart Images

Figure 2025025025000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an anticorrosive composition and an anticorrosive sheet using the same. [Background technology]
[0002] Steel structures including steel pipe piles, steel sheet piles, and steel pipe sheet piles installed on ocean or river quays, piers, bridge piers, etc. are prone to corrosion due to long-term exposure to severe deteriorating environments, and are therefore usually subjected to anticorrosion treatment. Conventional anticorrosion treatments include coating with an anticorrosion composition and attaching an anticorrosion sheet. For example, Patent Documents 1 and 2 describe an anticorrosion sheet in which an anticorrosive material made of a mixture of rubber and asphalt is placed on the surface of a sheet-like exterior material (base sheet) made of synthetic rubber or the like. Patent Documents 1 and 2 do not describe the specific composition of the anticorrosive material. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Utility Model Application Publication No. 58-38806 [Patent Document 2] Japanese Utility Model Publication No. 61-23097 Summary of the Invention [Problem to be solved by the invention]
[0004] Conventionally, petrolatum-based anticorrosive materials, which are mainly composed of petrolatum, have been widely used as anticorrosive materials. However, petrolatum-based anticorrosive materials have problems such as 1) the phenomenon of oil seeping out over time (oil leakage), 2) in anticorrosive sheets in which a petrolatum-based anticorrosive material is applied to the surface of a base sheet, defects with reduced anticorrosive performance occur due to uneven application, and 3) after application, parts of the anticorrosive material sag downwards under its own weight, causing deformation. There is a demand for an anticorrosive material that can provide anticorrosive effects equal to or greater than those of petrolatum-based anticorrosive materials without causing such problems.
[0005] The object of the present invention is to provide a corrosion prevention technology that can eliminate the drawbacks of the conventional technology described above, and more specifically, to provide a corrosion prevention composition, a corrosion prevention sheet, and a corrosion prevention method for steel structures that have excellent corrosion prevention effects. [Means for solving the problem]
[0006] The present inventors have conducted various studies on new anticorrosive agents to replace petrolatum-based anticorrosive agents, and have found that a waterproof sheet using an asphalt-based material for the waterproof layer is useful. This waterproof sheet has been conventionally used for purposes such as covering the base of a building or structure. Further studies have been conducted based on this waterproof sheet, and have found that a composition containing an asphalt base material containing asphalt and a styrene-based resin, a specific modifier, and having a penetration within a specific range exhibits anticorrosive effects equal to or greater than those of petrolatum-based anticorrosive agents, and is also excellent in applicability to objects to be protected from corrosion.
[0007] The present invention has been made based on the above findings, and provides an anticorrosion composition which comprises an asphalt base material containing asphalt and a styrene-based resin, and one or more modifiers selected from a styrene-butadiene-styrene block copolymer and a styrene-ethylene-butylene-styrene block copolymer, and which has a penetration of 60 to 500 at a product temperature of 25±0.1°C. The present invention also relates to a method for producing the anticorrosive composition of the present invention, comprising the steps of mixing the asphalt base material with the modifier and stirring the mixture while heating it.
[0008] The present invention has also been made based on the above-mentioned findings, and is an anticorrosion sheet that is placed on the surface of an object to be protected and has an anticorrosion layer that comes into contact with the surface of the object to be protected during use, wherein the anticorrosion layer is made of the anticorrosion composition of the present invention.
[0009] The present invention has also been made based on the above findings, and provides a method for protecting a steel structure from corrosion, comprising the step of attaching the above-mentioned anticorrosive sheet of the present invention to a surface of the steel structure. Effect of the Invention
[0010] According to the present invention, there are provided an anticorrosion composition having excellent anticorrosion effect, an anticorrosion sheet, and a method for preventing corrosion of a steel structure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The corrosion-preventive composition of the present invention includes at least an asphalt base material and a modifier, the modifier being at least one selected from styrene-butadiene-styrene block copolymers (SBS) and styrene-ethylene-butylene-styrene block copolymers (SEBS).
[0012] The asphalt base material contains at least asphalt and a styrene-based resin. In the asphalt base material, the asphalt and the styrene-based resin are inseparably integrated. The asphalt base material is typically produced by mixing the asphalt and the styrene-based resin while heating them.
[0013] The asphalt may be any asphalt that has been conventionally used for road pavement, waterproof sheets, etc., without any particular limitation, and examples thereof include petroleum asphalts such as straight asphalt and blown asphalt, and natural asphalts such as lake asphalt, rock asphalt, oil sand, and asphaltite, and these may be used alone or in combination of two or more. Among these asphalts, straight asphalt is particularly preferred.
[0014] Examples of the styrene-based resin include homopolymers obtained by polymerizing a styrene-based monomer, and copolymers obtained by copolymerizing a styrene-based monomer with another monomer copolymerizable therewith, and these may be used alone or in combination of two or more. When the styrene-based resin is a copolymer, there is no limitation on the polymerization mode, but it is typically a block copolymer. A preferred example of the styrene-based resin is SBS.
[0015] The content of the asphalt in the asphalt base material is preferably 10 to 90 mass %, more preferably 40 to 90 mass %, based on the total mass of the asphalt base material. The content of the styrene-based resin in the asphalt base material is preferably 3.5 to 30 mass %, more preferably 5 to 25 mass %, based on the total mass of the asphalt base material.
[0016] The content of the asphalt base material in the anticorrosion composition of the present invention is preferably 0.1 to 99.9 mass %, more preferably 60 to 99.9 mass %, and even more preferably 90.0 to 99.9 mass %, based on the total mass of the anticorrosion composition.
[0017] The content of the modifier (SBS and / or SEBS) in the anticorrosion composition of the present invention is preferably 3.5 to 30 mass %, more preferably 5 to 15 mass %, based on the total mass of the anticorrosion composition.
[0018] The anticorrosive composition of the present invention may contain a tackifier. This can further improve the adhesion of the anticorrosive composition, thereby improving the adhesion of the anticorrosive composition to the object to be protected, and thus improving the anticorrosive effect. Examples of the tackifier include petroleum resins such as aromatic petroleum resins, alicyclic petroleum resins, and aliphatic petroleum resins, and these can be used alone or in combination of two or more. Among these tackifiers, aliphatic hydrocarbon resins are particularly preferred.
[0019] The content of the tackifier in the anticorrosion composition of the present invention is preferably 0.1 to 20 parts by mass, and more preferably 1 to 5 parts by mass, relative to 100 parts by mass of the asphalt base material in the anticorrosion composition.
[0020] The anticorrosive composition of the present invention may contain a stiffening agent. This improves the stiffness of the anticorrosive composition, and as a result, the workability can be improved. Examples of stiffening agents include metal particles such as iron, copper, tin, zinc, nickel, and stainless steel; metal oxide particles such as iron oxide, ferric oxide, iron oxide, ferrite, tin oxide, zinc oxide, zinc oxide, copper oxide, and aluminum oxide; metal salt particles such as calcium carbonate, calcium bicarbonate, barium carbonate, calcium sulfate, barium sulfate, aluminum sulfate, calcium sulfite, and magnesium hydroxide; mineral particles such as steelmaking slag, mica, clay, talc, wollastonite, diatomaceous earth, silica sand, and pumice powder; and inorganic fibers such as glass fibers and carbon fibers, and these can be used alone or in combination of two or more. Among these stiffening agents, calcium carbonate is particularly preferred.
[0021] The content of the stiffening agent in the anticorrosion composition of the present invention is preferably 10 to 60 parts by mass, and more preferably 20 to 50 parts by mass, relative to 100 parts by mass of the asphalt base material in the anticorrosion composition.
[0022] The anticorrosive composition of the present invention is characterized in that the penetration at a product temperature of 25±0.1° C. is 60 to 500. The penetration can be measured in accordance with JIS K 2207-1996 "Petroleum Asphalt". The penetration is a physical property value indicating the hardness of the anticorrosive composition, and the smaller the penetration value, the harder the anticorrosive composition is, and the larger the penetration value, the softer the anticorrosive composition is. If the penetration value is less than 60, the adhesiveness of the anticorrosive composition may be reduced, and if the penetration value exceeds 500, the rigidity of the anticorrosive composition may be reduced, and in any case, the workability of the anticorrosive composition may be reduced. The penetration value is preferably 30 to 500, more preferably 30 to 80. The penetration value can be adjusted by adjusting the content of asphalt and / or styrene-based resin, which are the main components of the asphalt base material.
[0023] The anticorrosive composition of the present invention is produced by mixing the asphalt base material with the modifier and stirring the mixture while heating it. The mixture may contain optional components including the tackifier and stiffening agent. The heating temperature of the mixture may be any temperature at which the asphalt and styrene-based resin contained in the mixture can melt, and may be appropriately set depending on the types of asphalt and styrene-based resin, etc., but is typically preferably 40 to 300°C, more preferably 80 to 200°C. The process can be carried out using a mixer used in producing a conventionally known composition mainly composed of asphalt.
[0024] The asphalt base material used in the above step is one that has been produced using asphalt and a styrene-based resin prior to the step. If, in the above step, asphalt and a styrene-based resin are used alone instead of the asphalt base material, the anticorrosive composition of the present invention cannot be obtained. The method for producing the anticorrosive composition of the present invention may include a first step of producing an asphalt base material, and a second step of mixing the asphalt base material produced in the first step with the modifier and stirring the mixture while heating it.
[0025] The anticorrosive composition of the present invention can be used as an anticorrosive coating material in the form of an amorphous paste having fluidity, but it is preferable to mold it into a sheet and use it as an anticorrosive sheet, since the characteristics of the anticorrosive composition can be utilized and it is advantageous not only in terms of anticorrosive effect but also in terms of workability. The anticorrosive sheet of the present invention will be described below.
[0026] The anticorrosion sheet of the present invention is used by being placed on the surface of an object to be protected from corrosion, and has an anticorrosion layer that contacts the surface of the object to be protected when in use, the anticorrosion layer being made of the anticorrosion composition of the present invention described above. The anticorrosion layer typically has adhesive properties and can be attached to the surface of the object to be protected from corrosion.
[0027] The thickness of the anticorrosion layer is not particularly limited, but from the viewpoint of the balance between anticorrosion effect and workability, it is preferably 1 to 10 mm, more preferably 2 to 3 mm.
[0028] The anticorrosive sheet of the present invention may be in a form including only an anticorrosive layer (hereinafter also referred to as "first embodiment"), or may include other layers in addition to the anticorrosive layer. A specific example of the latter is a form including a non-adhesive base sheet on the surface of which an anticorrosive layer is provided (hereinafter also referred to as "second embodiment"). The second embodiment is typically a two-layer structure in which an anticorrosive layer is provided only on one side of the base sheet.
[0029] In the second embodiment, the base sheet may be a non-adhesive sheet material to which the anticorrosive layer can be fixed, for example, a film, a woven fabric, a non-woven fabric, paper, or aluminum foil. A particularly preferred base sheet is a film made of a synthetic resin. Examples of synthetic resins that are materials for forming the base sheet made of a film include polyethylene (PE), polypropylene (PP), and polyethylene terephthalate (PET), and these may be used alone or in combination of two or more. Among these synthetic resins, PE is particularly preferred.
[0030] The thickness of the base sheet is not particularly limited, but from the viewpoint of the balance between strength and workability, it is preferably 0.001 to 0.1 mm, and more preferably 0.005 to 0.015 mm.
[0031] The anticorrosive sheet of the first embodiment can be produced by forming a molten anticorrosive composition into a sheet shape. The anticorrosive sheet of the second embodiment can be produced by applying a molten anticorrosive composition to a substrate sheet, and then cooling and solidifying the anticorrosive composition. A known application method such as a bar coating method can be used to apply the molten anticorrosive composition to the substrate sheet.
[0032] The anticorrosion sheet of the present invention is suitable for the corrosion protection of various steel structures such as steel pipe piles, steel sheet piles, and steel pipe sheet piles. The method for protecting a steel structure from corrosion using the anticorrosion sheet of the present invention includes at least a step of attaching the anticorrosion sheet to the surface (surface to be protected from corrosion) of the steel structure. Typically, such a corrosion protection method is completed by carrying out a surface preparation such as removing dirt from the surface to be protected from corrosion, and then attaching the anticorrosion sheet so that the anticorrosion layer is in contact with the surface to be protected from corrosion.
[0033] If necessary, the outer surface of the anticorrosive sheet attached to the surface to be protected from corrosion (the surface opposite to the surface to be protected from corrosion) may be covered with a protective cover. The protective cover is intended to protect the anticorrosive sheet from external impact, and examples thereof include synthetic resin protective covers and metallic protective covers such as seawater-resistant stainless steel and titanium. A preferred example of the protective cover is one made of fiber-reinforced plastic. Fiber-reinforced plastic contains resin such as thermosetting resin and thermoplastic resin, and fiber such as glass fiber, carbon fiber, and organic fiber.
[0034] The anticorrosion sheet of the present invention can be applied by a simple operation of simply attaching the sheet to the surface to be protected via the anticorrosion layer, and is less susceptible to the above-mentioned problems seen in petrolatum-based anticorrosive materials, and can exhibit an anticorrosion effect equal to or greater than that of petrolatum-based anticorrosive materials. The anticorrosion sheet of the present invention has an anticorrosion layer that is stretchable and has excellent conformability to the surface to be protected from corrosion, so that the anticorrosion layer easily adheres to the surface to be protected from corrosion, which is one of the reasons why the anticorrosion sheet exhibits an excellent anticorrosion effect. In particular, a corrosion protection sheet (one type of the second embodiment) in which a corrosion protection layer is disposed on only one side of a base sheet can be stored in the form of a sheet roll in which the corrosion protection sheet is a long strip that is wound up in one direction before use, making it easy to secure storage space.When in use, the surface of the corrosion protection sheet facing the user (the surface opposite the surface that comes into contact with the surface to be protected from corrosion) is made of the base sheet and is not adhesive, so that inconveniences such as corrosion protection sheets sticking together during the process of attaching the sheet to the surface to be protected from corrosion are less likely to occur, making it easy to apply.
[0035] The anticorrosive composition and anticorrosive sheet of the present invention can be used for anticorrosive purposes for various structures, but are particularly useful for anticorrosive purposes for water structures. The term "water structure" as used herein refers to a structure including members such as steel materials installed in the ocean or river or in the vicinity thereof, and specific examples include steel structures including steel pipe piles, steel sheet piles, and steel pipe sheet piles installed on ocean or river quays, piers, bridge piers, etc. EXAMPLES
[0036] Example 1 An asphalt base material, SBS (modifier), aliphatic hydrocarbon resin (tackifier), and calcium carbonate (rigidity imparting agent) were charged into a mixer, and the contents of the mixer were stirred and mixed while being heated so that the product temperature of the contents of the mixer reached 180°C, thereby producing the anticorrosive composition of Example 1. The anticorrosive composition of Example 1 had a softening point of 138°C, a Frass embrittlement point of -38°C, and a viscosity of 400 Pa S at a product temperature of 200°C. In producing the corrosion-preventing composition of Example 1, 7.9 parts by mass of SBS was used per 100 parts by mass of the asphalt base material, 2.6 parts by mass of the aliphatic hydrocarbon resin was used per 100 parts by mass of the asphalt base material, and 47.9 parts by mass of calcium carbonate was used per 100 parts by mass of the asphalt base material. The asphalt base material was produced by using straight asphalt having a penetration of 150 to 200 at a product temperature of 25±0.1° C. and SBS as raw materials, charging these raw materials into a mixer, and stirring and mixing the contents of the mixer while heating the contents so that the product temperature of the contents becomes 180° C. In the asphalt base material, the straight asphalt content was 82 mass% relative to the total mass of the asphalt base material, and the SBS content was 18 mass% relative to the total mass of the asphalt base material.
[0037] Comparative Example 1 Straight asphalt having a penetration of 150 to 200 at a product temperature of 25±0.1°C, SBS (modifier), and aliphatic hydrocarbon resin (tackifier) were charged into a mixer, and the contents of the mixer were stirred and mixed while being heated so that the product temperature of the contents of the mixer reached 180°C, thereby producing the anticorrosive composition of Comparative Example 1. The anticorrosive composition of Comparative Example 1 had a softening point of 145°C, a Frass embrittlement point of -32°C, and a viscosity of 1650 Pa S at a product temperature of 200°C.
[0038] Comparative Example 2 Commercially available blown asphalt (manufactured by Showa Chemical Industries, Ltd., product name "Fujiclean") was used as the anticorrosive composition of Comparative Example 2. The anticorrosive composition of Comparative Example 2 had a softening point of 106°C, a furth embrittlement point of -16°C, and a viscosity of 360 Pa S at a product temperature of 200°C.
[0039] [Manufacturing of anticorrosive sheets] A molten anticorrosive composition was applied to one side of a PE film (thickness 0.010 mm) as a base sheet, and then dried to produce an anticorrosive sheet having a configuration (the second embodiment) in which an anticorrosive layer having a thickness of 2 to 2.5 mm was disposed only on one side of the base sheet. As the anticorrosive composition, any one of the anticorrosive compositions of Example 1 and Comparative Examples 1 and 2 was used. In addition, a release paper was laminated on the surface of the anticorrosive layer (the surface opposite to the base sheet side) of the produced anticorrosive sheet. When using the anticorrosive sheet, the release paper is peeled off to expose the anticorrosive layer.
[0040] [Evaluation test] The tensile strength and adhesive strength of the anticorrosive sheets of Example 1 and Comparative Example 1 were measured by the following methods. The anticorrosive performance (corrosion rate) of the anticorrosive sheets of each Example and Comparative Example was evaluated by the following method. The results are shown in Table 1 below.
[0041] <Method of evaluating tensile strength> A dumbbell No. 2 shape is punched out from the anticorrosive sheet with the release paper laminated thereon using a punching blade, and the punched anticorrosive sheet is pressed in the thickness direction to adjust the thickness to 1.0±0.1 mm to prepare a measurement sample. The chuck distance of the tensile tester is set to 60 mm, and the measurement sample is fixed between the chucks. The chuck distance is then increased at a rate of 500 mm / min to elongate the measurement sample, and the tensile load at the time when the measurement sample breaks is recorded, and the tensile strength (unit: N / mm 2 The higher the tensile strength value, the stronger the resistance of the anticorrosion sheet to pulling, and the higher the evaluation is that the sheet has sufficient strength for practical use.
[0042] <Method for evaluating adhesive strength> The anticorrosive sheet with the release paper laminated thereon is pressed in the thickness direction to adjust the thickness to 1.0±0.1 mm to prepare a measurement sample. The release paper of the measurement sample is peeled off to expose the anticorrosive layer, and the measurement sample is pressed from the base sheet side with a hand roller while the anticorrosive layer is in contact with an iron plate to press the measurement sample onto the iron plate. An attachment having a square shape in plan view, 4 cm long and 4 cm wide, is fixed to the surface of the base sheet of the measurement sample using an epoxy resin adhesive, and the measurement sample is cut along the contour of the attachment. The attachment is set in a tensile tester, and the attachment is pulled in the thickness direction of the measurement sample at a speed of 100 mm / min. The tensile load at the time when the measurement sample is peeled off from the iron plate is recorded, and the adhesive strength (unit: N / cm) of the measurement sample is calculated based on the obtained value. 2 The larger the adhesive strength value, the higher the evaluation of the anticorrosion sheet, which indicates that the sheet has excellent adhesion to the surface to be protected from corrosion.
[0043] <Method of evaluating corrosion prevention performance> Four steel test pieces, each 2 cm long and 5 cm wide in plan view and rectangular in shape, are placed on the outer surface of a 20A polyvinyl chloride pipe (outer diameter 27.2 mm), and then a corrosion prevention sheet is wrapped around the four test pieces so that the entire outer surfaces of the test pieces are covered. The corrosion prevention sheet is wrapped around the test pieces so that the release paper is removed and the exposed corrosion prevention layer comes into contact with the outer surfaces of the test pieces. The test pieces are placed in the tank of a combined cycle test machine and a dry-wet repeated test is carried out. This test is carried out in accordance with JIS K 5600_7_9 :2006 The test is conducted in accordance with (General Test Methods for Paints - Part 7 - Section 9 Cyclic Corrosion Test Methods - Salt Spray / Dry / Wet) and there are three test times: 2808 hours, 7000 hours, and 10000 hours. After the test time has elapsed, the anti-corrosion sheet is removed from the test specimen and the four test pieces are collected. The thickness of each test piece is measured and the corrosion rate (unit: mm / y) is calculated from the measured thickness and the test time. The arithmetic average of the corrosion rates of the four pieces is regarded as the corrosion rate of the anti-corrosion sheet. The smaller the corrosion rate, the more excellent the corrosion prevention performance of the anti-corrosion sheet is evaluated.
[0044] [Table 1]
[0045] As shown in Table 1, the anticorrosive composition of Comparative Example 1 is a so-called modified asphalt containing SBS in addition to asphalt, and although it has superior anticorrosive performance compared to the anticorrosive composition of Comparative Example 2, which is a normal asphalt that does not contain a styrene-based resin such as SBS, it does not reach the anticorrosive performance of the anticorrosive composition of Example 1, and the anticorrosive composition of Example 1 was also superior in terms of tensile strength and adhesive strength. The anticorrosive composition of Example 1 differs from the anticorrosive composition of Comparative Example 1, which does not contain an asphalt base material in which asphalt and SBS are integrated, in that it contains an asphalt base material, and therefore it is clear that the asphalt base material is effective in improving the tensile strength, adhesive strength and anticorrosive performance of the anticorrosive composition.
Claims
1. An asphalt base material containing asphalt and a styrene-based resin; and one or more modifiers selected from a styrene-butadiene-styrene block copolymer and a styrene-ethylene-butylene-styrene block copolymer; A corrosion prevention composition having a penetration of 60 to 500 at a product temperature of 25±0.1°C.
2. 10. The corrosion protection composition of claim 1, further comprising one or more tackifiers selected from aliphatic hydrocarbon resins.
3. The anticorrosive composition according to claim 1 or 2, further comprising calcium carbonate.
4. The anticorrosion composition according to claim 1 or 2, which is used for corrosion prevention of aquatic structures.
5. A method for producing the anticorrosive composition according to claim 1 or 2, comprising the steps of: A method for producing a corrosion-protecting composition, comprising the steps of mixing the asphalt base material and the modifier, and stirring the mixture while heating it.
6. A corrosion protection sheet that is disposed on a surface of an object to be protected from corrosion and has a corrosion protection layer that contacts the surface of the object to be protected from corrosion during use, 3. A corrosion-prevention sheet, wherein the corrosion-prevention layer comprises the corrosion-prevention composition according to claim 1 or 2.
7. The corrosion protection sheet according to claim 6, comprising a non-adhesive base sheet, the corrosion protection layer being provided on a surface of the base sheet.
8. A method for preventing corrosion of a steel structure, comprising the step of attaching the corrosion prevention sheet according to claim 6 to a surface of the steel structure.
Citation Information
Patent Citations
Prevention of corrosion of fitted joint part of steel sheet pile
JP1986049030A
Self-adhesive sheet for steel material corrosion-resistant coating
JP1997239895A
Modified asphalt composition and waterproof sheet
JP2018002997A
The corrosion protective coating
JP1983038806U
Capturing [...][...]
JP1986023097U